Teatr as one of the most influential means of aesthetic education - Юдін, Микола (Pedagogy of Higher and Secondary Education, 2013)
Yudin N. M.Teatr as one of the most influential means of aesthetic education. In the article it is shown the problems of esthetic upbringing of children and youth on the modern stage of building Ukrainian society. Also it is shown the perspectives of the role of the theatre in this process.